Developing three-dimensional groundwater flow modeling for the Erbil Basin using Groundwater Modeling System (GMS) - Jwan Sabah Mustafa; Dana Khider Mawlood (Journal of Groundwater Science and Engineering, 2024)
This study presents the development of a comprehensive three-dimensional groundwater flow model for the Erbil Basin utilizing the Groundwater Modeling System (GMS). The Erbil Basin, situated in the Kurdistan Region of Iraq, is a vital water resource area facing increasing water demands and environmental challenges. The three-dimensional nature of the groundwater flow system is crucial for accurately understanding and managing water resources in the basin. The modeling process involved data collection, geological and hydrogeological characterization, conceptual model development, and numerical simulation using GMS software MODFLOW 2000 package. Various parameters such as hydraulic conductivity, recharge rates, and boundary conditions were integrated into the model to represent the complex hydrogeological conditions of the basin. Model calibration was performed by comparing simulated groundwater levels with observed data from monitoring wells across the basin, using the automatic calibration method of automated Parameter Estimation (PEST). Pilot points were applied to adjust the hydraulic conductivity in the model area spatially. Sensitivity analysis was conducted to assess the influence of key parameters on model predictions and to identify areas of uncertainty. The developed three-dimensional groundwater flow model provides valuable insights into the dynamics of groundwater flow, recharge-discharge mechanisms, and potential impacts of future scenarios such as climate change and water resource management strategies. It serves as a useful tool for decision-makers, water resource managers, and researchers to evaluate different management scenarios and formulate sustainable groundwater management policies for the Erbil Basin. In conclusion, this study demonstrates the effectiveness of using GMS for developing three-dimensional groundwater flow models in complex hydrogeological settings like the Erbil Basin, contributing to improved understanding and management of groundwater resources in the region.